Chemotherapy options versus “novel” therapies: how should we treat patients with malignant pleural mesothelioma - Disselhorst, Maria J. (Transl Lung Cancer Res, 2020)
Today there are several options for the treatment of patients with malignant pleural mesothelioma (MPM). The therapeutic arsenal has expanded from only chemotherapy with or without surgery in selected cases to a variety of new compounds that target the malignant cell or its micro-environment. Immunotherapy has been the latest achievement and now single arm and randomized studies are being presented. A renewed interest has occurred in the combination of surgery, chemotherapy and radiation therapy. In this review we present the available data on previous and running studies and try to give a recommendation how to select the best patient for the most optimal therapy.